The effects of leadership styles on the job satisfaction of the employees in family companies that service the construction industry - Zengin, Seray (My University, 2020)
ABSTRACTTHE EFFECTS OF LEADERSHIP STYLES ON THE JOB SATISFACTION OF THE EMPLOYEES IN FAMILY COMPANIES THAT SERVICE THE CONSTRUCTION INDUSTRYIt does not seem possible to manage organizations and institutions with the traditional leader and management models of the past, to ensure the job satisfaction of their employees, and to respond to the rapidly changing and complex market. Today, attention is focused on the leaders and the leader is considered as the main actor of success, the architect of change, the person who plans the future, creates a vision and makes it a part of his personality. Today, many leadership styles are mentioned. Leadership styles are approaches used to motivate followers. Leadership is not a one size fits all phenomenon. Leadership styles should be chosen and adapted to suit organizations, situations, groups and individuals. Thus, the tools and quality used for effective management of information will increase.In today's world, where management, especially leadership, is identified with vision, the definitions of leadership are associated with the characteristics of the leader, vision formation and sustainability. The twenty-first century emerges as a period in which vision and visionary leadership dominate the administration. Studies aimed at increasing employees' job satisfaction and, consequently, their performance show that leaders have a very important place in this regard.In this study, it was examined how different leadership styles in family companies operating in the construction sector affect the job satisfaction of employees. In the theoretical part of the study, the concepts of family companies, leadership and job satisfaction are emphasized, and the relationships between these concepts are discussed. In the empirical part of the study, data collection based on a questionnaire, which includes employees in family companies, will be carried out and statistical analysis of the data has been made. Personal Information Scale, Leadership Scale and Minnesota Job Satisfaction Scale were used as data collection tools. In line with the information obtained as a result of this research, the effect of different leadership styles in family companies on job satisfaction levels of employees was determined. CONTENTSPageÖZETiiiABSTRACTvACKNOWLEDGEMENTSviiCONTENTSviiiLIST OF TABLESxiiiINTRODUCTION1CHAPTER I2PURPOSE, IMPORTANCE21.1. PURPOSE OF THE RESEARCH21.2. THE IMPORTANCE OF RESEARCH31.3. HYPOTHESES OF THE RESEARCH41.4. SCOPE AND LIMITATIONS OF THE RESEARCH5CHAPTER II6PREVIOUS STUDIES62.1. FAMILY BUSINESS CONCEPT62.2. THE MAIN FEATURES OF FAMILY COMPANIES72.3. ADVANTAGES AND DISADVANTAGES OF FAMILY COMPANIES82.4. MANAGEMENT IN FAMILY COMPANIES102.4.1. Centralized Management102.4.2. Participatory Management112.5. MANAGEMENT PROBLEMS IN FAMILY COMPANIES122.5.1. Planning Issues132.5.2. Organization Issues132.5.3. Coordination Issues142.5.4. Control and Audit Issues142.5.5. Employee and Employment Issues152.5.6. Financing Issues152.5.6. Execution Issues15CHAPTER III17THE LEADERSHIP CONCEPT AND RELATIONSHIP BETWEEN LEADERSHIP AND BUSINESS SATISFACTION173.1. LEADERSHIP CONCEPT AND THEORIES173.1.1. Definition of Leadership173.1.2. Differences and Similarities Between Leadership and Management183.1.3. Reasons to Need Leadership193.1.4. Leadership Theories193.1.4.1. Great Man Theory203.1.4.2. Personality Traits Theory203.1.4.3. Contingency Theories213.1.4.4. Situational Theory213.1.4.5. Behavioral Theory213.1.4.6. Participative Theory223.1.4.7. Interactive/ Management Theory223.1.4.8. Transformational Theory233.1.4.9. Paternalist Leadership233.2. RELATIONSHIP BETWEEN LEADERSHIP AND JOB SATISFACTION243.2.1. Definition of Job Satisfaction243.2.2. The first job satisfaction Studies253.2.3. Factors Affecting Job Satisfaction263.2.3.1. Personal Issues263.2.3.1.1. Age263.2.3.1.2. Gender273.2.3.1.3. Education Level273.2.3.1.4. Culture283.2.3.1.5. Intelligence Level283.2.3.1.6. Career283.2.3.1.7. Job Experience293.2.3.2. Organizational Factors293.2.3.2.1. General View of the Job (Job Level)293.2.3.2.2. Structural Feature of the Work293.2.3.2.3. Difficulty Level of The Job303.2.3.2.4. Internal Feature of the Work303.2.3.2.5. Salary-Wage303.2.3.2.6. Promotion303.2.3.2.7. Human Relations303.2.3.2.8. Communication313.2.3.2.9. Group of Employees313.2.3.2.10. Social View of the Business313.2.3.2.11. Working Conditions313.2.3.2.12. Work safety313.2.3.3. Social and Environmental Factors323.3. THEORIES ON JOB SATISFACTION AND MOTIVATION RELATIONSHIP323.3.1. Content Theories323.3.1.1. Maslow's Hierarchy of Needs333.3.1.2. Alderfer's ERG Theory333.3.1.3. Herzberg’s Double Factor Theory343.3.1.4. Job Features Model353.3.1.5. Success-Power Theory353.3.2. Process Theories353.3.2.1. Vroom's Expectation Theory353.3.2.2. Lawler and Porter's Enhanced Expectation Theory363.3.2.3. Reward Justice (Equality)Theory363.3.2.4. Purpose Theory363.3.2.5. Conditioning and Reinforcement Theory373.4. LEADERSHIP AND JOB SATISFACTION373.4.1. Leadership-Organizational Justice Perception Relationship373.4.2. Leadership-Organizational Commitment Relationship383.4.3. The Relationship between Leadership and Job Satisfaction403.4.4. Leadership-Organizational Citizenship Behavior Relationship403.4.5. Distributive Justice Perception-Organizational Citizenship Behavior Relationship403.4.6. Distributive Justice Perception-Job Satisfaction Relationship413.4.7. Job Satisfaction-Organizational Commitment Relationship41CHAPTER IV42MATERIAL AND METHOD424.1. THE MODEL OF THE RESEARCH424.2. UNIVERSE AND SAMPLING OF THE STUDY424.3. DATA COLLECTION METHOD AND TOOL424.4. DATA ANALYSIS434.4.1. Data Collecting Method444.4.2. Factor Analyses474.4.2.1. Relability Analyses (Leadership Scale)584.4.2.2. Minnesota Scale614.4.2.3. Reliability Analysis ( Leadership Scale)72CHAPTER V74RESULTS AND DISCUSSION745.1. ANOVA745.2. CORRELATION COEFFICIENT845.3. LIKERT ANALYZES895.4. REGRESSION ANALYSIS915.4.1. Leadership915.4.2. Minnesota95CONCLUSION101ANNEXES106ANNEX 1: ANKET FORMU106REFERENCES112

ÖZETİNŞAAT SEKTÖRÜNDE HİZMET VEREN AİLE ŞİRKETLERİNDE, LİDERLİK TARZLARININ ÇALIŞANLARIN İŞ TATMİNİ ÜZERİNDEKİ ETKİLERİGeçmişin geleneksel lider ve yönetim modelleri ile örgütleri ve kurumları idare etmek, çalışanlarının iş tatminini sağlamak, bu kurumların, hızla değişen karmaşık yapıdaki piyasaya cevap verebilmesi pek te mümkün görülmemektedir. Günümüzde dikkatler liderler üzerinde yoğunlaşmakta ve lider, başarının asıl aktörü, değişimin mimarı, geleceği planlayan, vizyon oluşturan ve bunu kişiliğinin bir parçası haline getiren kişi olarak değerlendirilmektedir. Günümüzde pek çok liderlik tarzlarından söz edilmektedir. Liderlik tarzları, takipçileri motive etmek için kullanılan yaklaşımlardır. Liderlik “tek beden herkese uyar” fenomeni değildir. Liderlik tarzları, organizasyonlara, durumlara, gruplara ve bireylere uyacak şekilde seçilmeli ve uyarlanmalıdır. Böylelikle, bilginin etkili bir şekilde yönetilmesi için kullanılan araçlar ve kalitesi de artacaktır. Yönetim, özellikle liderliğin vizyon ile özdeşleştiği günümüzde, liderlik tanımları liderin özellikleri, vizyon oluşturma ve sürdürebilme konuları ile özdeşleştirilmektedir. Yirmi birinci yüzyıl, vizyon ve vizyoner liderliğin yönetime hâkim olduğu bir dönem olarak karşımıza çıkmaktadır. Çalışanların iş tatmini ve buna bağlı olarak performanslarını artırmaya yönelik çalışmalar liderlerin bu konuda çok önemli bir yere sahip olduklarını göstermektedir.Bu çalışmada inşaat sektöründe faaliyet gösteren aile şirketlerindeki farklı liderlik biçimlerinin, çalışanların iş tatminlerini ne şekilde etkilediği incelenmiştir. Çalışmanın teorik kısmında aile şirketleri, liderlik ve iş tatmini kavramları üzerinde durulmuş, bu kavramların birbiriyle olan ilişkileri ele alınmıştır. Çalışmanın ampirik kısmında ise, aile şirketlerindeki çalışanları kapsayan, ankete dayalı veri toplama işlemi gerçekleştirilecek ve verilerin istatistiksel analizleri yapılmıştır. Veri toplama aracı olarak anketlerde Kişisel Bilgiler Ölçeği, Liderlik Ölçeği ve Minnesota İş Tatmini Ölçeği temel alınmıştır. Bu araştırmanın sonucunda elde edilen bilgiler doğrultusunda, aile şirketlerindeki farklı liderlik biçimlerinin çalışanların iş tatmin düzeylerine etkisi belirlenmiştir.CONTENTSPageÖZETiiiABSTRACTvACKNOWLEDGEMENTSviiCONTENTSviiiLIST OF TABLESxiiiINTRODUCTION1CHAPTER I2PURPOSE, IMPORTANCE21.1. PURPOSE OF THE RESEARCH21.2. THE IMPORTANCE OF RESEARCH31.3. HYPOTHESES OF THE RESEARCH41.4. SCOPE AND LIMITATIONS OF THE RESEARCH5CHAPTER II6PREVIOUS STUDIES62.1. FAMILY BUSINESS CONCEPT62.2. THE MAIN FEATURES OF FAMILY COMPANIES72.3. ADVANTAGES AND DISADVANTAGES OF FAMILY COMPANIES82.4. MANAGEMENT IN FAMILY COMPANIES102.4.1. Centralized Management102.4.2. Participatory Management112.5. MANAGEMENT PROBLEMS IN FAMILY COMPANIES122.5.1. Planning Issues132.5.2. Organization Issues132.5.3. Coordination Issues142.5.4. Control and Audit Issues142.5.5. Employee and Employment Issues152.5.6. Financing Issues152.5.6. Execution Issues15CHAPTER III17THE LEADERSHIP CONCEPT AND RELATIONSHIP BETWEEN LEADERSHIP AND BUSINESS SATISFACTION173.1. LEADERSHIP CONCEPT AND THEORIES173.1.1. Definition of Leadership173.1.2. Differences and Similarities Between Leadership and Management183.1.3. Reasons to Need Leadership193.1.4. Leadership Theories193.1.4.1. Great Man Theory203.1.4.2. Personality Traits Theory203.1.4.3. Contingency Theories213.1.4.4. Situational Theory213.1.4.5. Behavioral Theory213.1.4.6. Participative Theory223.1.4.7. Interactive/ Management Theory223.1.4.8. Transformational Theory233.1.4.9. Paternalist Leadership233.2. RELATIONSHIP BETWEEN LEADERSHIP AND JOB SATISFACTION243.2.1. Definition of Job Satisfaction243.2.2. The first job satisfaction Studies253.2.3. Factors Affecting Job Satisfaction263.2.3.1. Personal Issues263.2.3.1.1. Age263.2.3.1.2. Gender273.2.3.1.3. Education Level273.2.3.1.4. Culture283.2.3.1.5. Intelligence Level283.2.3.1.6. Career283.2.3.1.7. Job Experience293.2.3.2. Organizational Factors293.2.3.2.1. General View of the Job (Job Level)293.2.3.2.2. Structural Feature of the Work293.2.3.2.3. Difficulty Level of The Job303.2.3.2.4. Internal Feature of the Work303.2.3.2.5. Salary-Wage303.2.3.2.6. Promotion303.2.3.2.7. Human Relations303.2.3.2.8. Communication313.2.3.2.9. Group of Employees313.2.3.2.10. Social View of the Business313.2.3.2.11. Working Conditions313.2.3.2.12. Work safety313.2.3.3. Social and Environmental Factors323.3. THEORIES ON JOB SATISFACTION AND MOTIVATION RELATIONSHIP323.3.1. Content Theories323.3.1.1. Maslow's Hierarchy of Needs333.3.1.2. Alderfer's ERG Theory333.3.1.3. Herzberg’s Double Factor Theory343.3.1.4. Job Features Model353.3.1.5. Success-Power Theory353.3.2. Process Theories353.3.2.1. Vroom's Expectation Theory353.3.2.2. Lawler and Porter's Enhanced Expectation Theory363.3.2.3. Reward Justice (Equality)Theory363.3.2.4. Purpose Theory363.3.2.5. Conditioning and Reinforcement Theory373.4. LEADERSHIP AND JOB SATISFACTION373.4.1. Leadership-Organizational Justice Perception Relationship373.4.2. Leadership-Organizational Commitment Relationship383.4.3. The Relationship between Leadership and Job Satisfaction403.4.4. Leadership-Organizational Citizenship Behavior Relationship403.4.5. Distributive Justice Perception-Organizational Citizenship Behavior Relationship403.4.6. Distributive Justice Perception-Job Satisfaction Relationship413.4.7. Job Satisfaction-Organizational Commitment Relationship41CHAPTER IV42MATERIAL AND METHOD424.1. THE MODEL OF THE RESEARCH424.2. UNIVERSE AND SAMPLING OF THE STUDY424.3. DATA COLLECTION METHOD AND TOOL424.4. DATA ANALYSIS434.4.1. Data Collecting Method444.4.2. Factor Analyses474.4.2.1. Relability Analyses (Leadership Scale)584.4.2.2. Minnesota Scale614.4.2.3. Reliability Analysis ( Leadership Scale)72CHAPTER V74RESULTS AND DISCUSSION745.1. ANOVA745.2. CORRELATION COEFFICIENT845.3. LIKERT ANALYZES895.4. REGRESSION ANALYSIS915.4.1. Leadership915.4.2. Minnesota95CONCLUSION101ANNEXES106ANNEX 1: ANKET FORMU106REFERENCES112
Keywords: Business; İŞ TATMİNİ; İşletme; LEADERSHIP; LİDERLİK JOB SATISFACTION